ESTIMASI NILAI DATA HILANG MENGGUNAKAN IMPUTASI GANDA DENGAN METODE REGRESI - , MONICA RINDAYU G. K. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Data is one of the important points in every data analysis as it is impossible to conduct data analysis without data. The data used is expected to be a good data. In fact, it is commonly found that the data doesnât meet the expectation. Incomplete data causes the difficulty in drawing the conclusion. If missing data are ignored, it causes the conclusion are bias or invalid. Therefore, there are various methods for estimating the missing value. One of them is multiple imputation using regression method. This method is used to estimate the missing value on the dependent variable. The discussion ended with a case study of the missing data value estimation in a percentage variable of the poor inhabitants.